How emotional abilities modulate the influence of early life stress on hippocampal functioning - Aust, Sabine (Oxford University Press, 2014)
Early life stress (ELS) is known to have considerable influence on brain development, mental health and affective functioning. Previous investigations have shown that alexithymia, a prevalent personality trait associated with difficulties experiencing and verbalizing emotions, is particularly related to ELS. The aim of the present study was to investigate how neural correlates of emotional experiences in alexithymia are altered in the presence and absence of ELS. Therefore, 50 healthy individuals with different levels of alexithymia were matched regarding ELS and investigated with respect to neural correlates of audio-visually induced emotional experiences via functional magnetic resonance imaging. The main finding was that ELS modulated hippocampal responses to pleasant (>neutral) stimuli in high-alexithymic individuals, whereas there was no such modulation in low-alexithymic individuals matched for ELS. Behavioral and psychophysiological results followed a similar pattern. When considered independent of ELS, alexithymia was associated with decreased responses in insula (pleasant > neutral) and temporal pole (unpleasant > neutral). Our results show that the influence of ELS on emotional brain responses seems to be modulated by an individual’s degree of alexithymia. Potentially, protective and adverse effects of emotional abilities on brain responses to emotional experiences are discussed.